2014
DOI: 10.1002/eji.201343956
|View full text |Cite
|
Sign up to set email alerts
|

Differences in T‐cell responses between Mycobacterium tuberculosis and Mycobacterium africanum‐infected patients

Abstract: In The Gambia, Mycobacterium tuberculosis (Mtb) and Mycobacterium africanum (Maf) are major causes of tuberculosis (TB). Maf is more likely to cause TB in immune suppressed individuals, implying differences in virulence. Despite this, few studies have assessed the underlying immunity to the two pathogens in human. In this study, we analyzed T-cell responses from 19 Maf-and 29 Mtb-infected HIV-negative patients before and after TB chemotherapy following overnight stimulation of whole blood with TB-specific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Samples without stimulus were used as negative controls to allow calculation of the magnitude of the induced responses. Phytohemagglutinin (PHA; 5 µg/mL), purified protein derivative (PPD; Staten Serum Institute, Denmark) and a pool of 35 overlapping 15 mer peptides (2.5 µg/mL) derived from the 6 kDa Early Secreted Antigenic Target and the Culture Filtrate Protein-10 protein (ESAT-6/CFP-10) were used as positive controls (Tientcheu et al, 2014). Antigens were stimulated in triplicate and after seven days incubation at 37°C in a humidified CO 2 incubator, supernatants were removed for assay of IFN-γ.…”
Section: Methodsmentioning
confidence: 99%
“…Samples without stimulus were used as negative controls to allow calculation of the magnitude of the induced responses. Phytohemagglutinin (PHA; 5 µg/mL), purified protein derivative (PPD; Staten Serum Institute, Denmark) and a pool of 35 overlapping 15 mer peptides (2.5 µg/mL) derived from the 6 kDa Early Secreted Antigenic Target and the Culture Filtrate Protein-10 protein (ESAT-6/CFP-10) were used as positive controls (Tientcheu et al, 2014). Antigens were stimulated in triplicate and after seven days incubation at 37°C in a humidified CO 2 incubator, supernatants were removed for assay of IFN-γ.…”
Section: Methodsmentioning
confidence: 99%
“…Further support for our findings stems from other genomic epidemiological studies. Nonsynonymous SNPs (albeit different from the ones identified in this study) and a frameshift mutation in espE were found to be more common in Mycobacterium africanum strains relative to H37Rv (28) and to be implied in their reduced ability to induce a CD4-cell ESAT-6-induced IFN-g host response (29,30). Similarly, in a previous study, researchers identified a large sequence polymorphism associated with clustering in a gene (MT1801) encoding molybdopterin oxidoreductase, which is also encoded by Rv0197 (31).…”
Section: Discussionmentioning
confidence: 51%
“…This result is comparable to an earlier report comparing mutations within regulatory proteins between Mtbss and M. bovis , which found most of the M. bovis to harbor majority of the mutations 36 . As mutations within some regulatory proteins have been associated with attenuated virulence 3840 , our observation could account for the reported attenuated virulence of Maf relative to Mtbss 14,15,17,41 . This calls for further comparative studies of regulatory proteins between L5, L6 and other MTBC lineages to ascertain the role of regulatory proteins.…”
Section: Discussionmentioning
confidence: 61%
“…Some evidence in support of the first hypothesis is the reported association of Maf (L6) with HIV co-infection, attenuated ESAT-6 responses and delayed progression to active disease relative to Mtbss 9,1316 . In addition, both Maf lineages as well as Mtbss L1, together described as “ancestral” MTBC lineages, have been shown to elicit a stronger early production of pro-inflammatory cytokines compared to the “modern” MTBBC L2, L3 and L4 17 .…”
Section: Introductionmentioning
confidence: 86%